Critical perspectives on activity: Explorations across education, work, and everyday life - Sawchuk, Peter H.; Duarte, Newton [UNESP]; Elhammoumi, Mohamed (Cambridge University Press (CUP), 2006)
The last two decades have seen an international explosion of interest in theories of mind, culture, and activity. This book includes a diverse array of theoretical perspectives from international scholars in the fields of education, psychology, philosophy, sociology, anthropology, communications, industrial relations, and business studies. Broken into three main sections (education, work, and everyday life) each chapter emerges from an analysis of practice and learning as social cultural participation and historical change in relation to the concept of activity, contradiction, and struggle.